Moral and Spiritual Meaning-Making in Substance Use Recovery: An Interpretive Qualitative Study of Da’wah Counseling - Rosidi, Rosidi; Subandi, Subandi; Mubasit, Mubasit (Islamic Guidance and Counseling Journal, 2026)
Substance use rehabilitation is commonly approached through biomedical and psychosocial frameworks, with comparatively limited attention to how moral and spiritual meanings are constructed within recovery processes. In contexts where religious belief systems are embedded in everyday life, recovery may involve not only behavioral change but also the reinterpretation of self, responsibility, and life purpose. This study explores how individuals undergoing rehabilitation interpret and make sense of their recovery experiences through a da’wah counseling approach. An interpretive qualitative study was conducted at the National Narcotics Agency (BNN) in Lampung, Indonesia. Data were generated through in-depth interviews involving counselors and clients undergoing rehabilitation. Analysis focused on interpreting how participants understood and negotiated their experiences, using an iterative process of coding, comparison, and thematic interpretation. Findings indicate that da’wah counseling was experienced by participants as a process of moral and spiritual meaning-making rather than solely as religious instruction. Through guided reflection and value-oriented dialogue, clients reinterpreted their past behaviors, reframed recovery as a form of moral responsibility, and reconstructed a sense of self aligned with religious and social values. Practices such as remembrance (dzikir), repentance (taubah), and trust in God (tawakkul) were not only performed but imbued with personal meaning, serving as resources for managing emotional distress and sustaining behavioral change. Participants described recovery as a process of becoming more self-aware, emotionally regulated, and oriented toward purposeful living. These findings do not claim effectiveness but offer interpretive insight into how recovery is shaped through moral and spiritual meaning-making within a specific cultural and institutional context. The study contributes to culturally responsive counseling by illustrating how religious concepts can function as interpretive resources through which individuals understand and sustain change.